Consumers’ willingness to pay premium under the influence of consumer community culture: From the perspective of the content creator - Ren, Jifan; Yang, Jialiang; Liu, Erhao; Huang, Fangfang (Frontiers in Psychology, 2022)
With the rise of live streaming commerce, the relationship between consumers and content creators on the short-video platforms has become closer, forming a peculiar culture and language in each consumer community, which promotes the short-video platforms to become a natural breeding ground for forming consumer communities. While such communities giving birth to its own language and culture from the interaction between content creators and consumers, this kind of co-creation can not only enhance the consumers’ trust to improve commodity premium space, but also strengthen the ties within the community and spread the information outside the communities, consequently, expand community scale. Based on the view of the value co-creation from the language and culture among content creators and consumers in the communities, this study starts from the point of product type, employs consumers' Willingness to Pay Premium (WoPP) as a proxy variable of brand advocacy in the co-creation of cultural and language values in consumer communities, conducts three single factor experiments between two groups. By analyzing the experimental results, this study identified the influence under the potential relationship mechanism, social comparison, and found another variable that can moderate the relationship, consumer trust, portrays the relationship between the product types of the live streaming commerce and the consumers’ WoPP, explores the mediating effect of social comparison and the moderate effect of consumer trust effect. This paper also analyzes and discusses the WoPP caused by the co-creation of cultural and language values co-created by creators and consumer communities.